2011
DOI: 10.3238/arztebl.2011.0653
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Target Treatment Versus Low-Frequency Electrostimulation for Anal Incontinence

Abstract: 3T is superior to LFS in the treatment of anal incontinence. The available evidence suggests that the success of 3T is based on the combined effect of biofeedback and medium-frequency stimulation. LFS of the type applied in this trial has no effect. 3T should be used in routine clinical practice instead of LFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 29 publications
3
26
0
1
Order By: Relevance
“…The group has published a RCT comparing 3T to standard EMG biofeedback in 2010 and another in 2011 comparing 3T to the more standardly used LFS. 33,36 The 2010 study was significantly underpowered because less than 40% of their subjects completed the 9-month treatment protocol, but the intention to treat analysis demonstrated improved continence in the 3T group. The 2011 study showed statistically significant improvements in continence in the 3T group compared with standard LFS; however, the LFS group did not have EMG biofeedback and the 3T group did.…”
Section: Summary Of Selected Trials Involving Both Biofeedback and Comentioning
confidence: 99%
“…The group has published a RCT comparing 3T to standard EMG biofeedback in 2010 and another in 2011 comparing 3T to the more standardly used LFS. 33,36 The 2010 study was significantly underpowered because less than 40% of their subjects completed the 9-month treatment protocol, but the intention to treat analysis demonstrated improved continence in the 3T group. The 2011 study showed statistically significant improvements in continence in the 3T group compared with standard LFS; however, the LFS group did not have EMG biofeedback and the 3T group did.…”
Section: Summary Of Selected Trials Involving Both Biofeedback and Comentioning
confidence: 99%
“…When judging the efficacy of the ES treatment or the combination of BF and ES (BF + ES), current type, current strength, and application mode are essential [ 6 10 ], as recently discussed by Schwandner et al [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although innumerable measures, scales and composite indices have been used, there is no acceptable gold standard or outcome measure. A selected list of recent RCTs spanning medical, biofeedback, injectable and surgical interventions are summarized in Table . This highlights the disparities in subject selection, trial design, outcome measures and risk of bias.…”
Section: Defining and Validating A Fi Endpointmentioning
confidence: 99%